The characteristics and changes of the natural social binary water cycle in the Upper Yellow River Basin under the influence of climate change and human activities: A review - Yuanwei Man; Meixue Yang; Xiaohua Gou; Guoning Wan; Yawen Li; Xuejia Wang (Journal of Hydrology: Regional Studies)
Study region: Upper Yellow River Basin (UYRB), China. Study focus: We provide a comprehensive overview of the changes in the natural social binary water cycle system in the UYRB from the perspectives of the atmosphere, hydrosphere, cryosphere, biosphere, and human society by summarizing previous research results. New hydrological insight for the region: Since the 1980s, the continuous temperature rise led to permafrost thawing, resulting in a decrease in runoff and an increase in groundwater in the UYRB. The ecological protection and high-quality development of human society continuously increase the demand for water resources. Especially the runoff of the river section in the human gathering area has significantly decreased and there has been an overexploitation of groundwater, resulting in a serious shortage of water resources. The future water supply and demand situation in the UYRB will be more severe. However, the current understanding of the natural social binary water cycle in the Upper Yellow River Basin is still insufficient, which seriously limits the high-quality development of human society in the UYRB. Among them, some erroneous conclusions can even provide misleading information for policy-making and cause serious manpower and resources loss. Natural social binary water cycle is still in initial stage in the UYRB, that is reflected in a lot of contradictions and shortcomings in past research. We propose four feasible research directions to comprehensively promote hydrometeorological research, providing effective guidance for the formulation of high-quality development policies in the UYRB.